THU0331 Do EEG Changes in SLE Correlate with SLE Disease Activity?. (23rd January 2014) - Atukorala, I.; Weeratunga, P.; Gunasekera, S.; Gunawardena, N.; Chang, T.
Abstract : Background: Subclinical electroencephalographic (EEG) changes are seen in patients with systemic lupus erythematosus (SLE), including those without central nervous system (CNS) involvement [1 ]. Baseline and paroxysmal EEG changes are seen in the majority, but temporo-limbic changes occur more commonly in those with seizures [2 ]. It is yet unknown if SLE disease activity correlates with EEG changes seen in SLE. Moreover, no particular EEG patterns have been described in in SLE patients with and without CNS involvement. An EEG marker of disease activity or CNS involvement will be critical in selecting patients with CNS lupus for aggressive immune suppression. Objectives: Describe the association of EEG changes with (1) SLE disease activity (2)CNS and non-CNS disease flares Methods: 70 subjects fulfilling the American College of Rheumatologists criteria for SLE were evaluated over one year. Patients with previous seizures not due to SLE including CNS infections, head injury & previous neurosurgical procedures were excluded. Socio demographic data, disease characteristics, British Isles Lupus Activity Group (BILAG) disease activity assessment, neuropsychiatric lupus screening questionnaire (NPSLEQ) and 30 minute awake EEGs were collected. Subjects were categorized to two groups depending on current disease activity: Group A-high disease activity (BILAG scores of A and B), Group B-low disease activity. 30min EEGs were read by an investigator blinded to patient information and group allocation. Results: Group A comprised of 20 (Mean age 32 (SD = 7.7)) and Group B comprised of 50 patients (Mean Age 33 (SD = 8.1). The majority were female (95% in Group A; 96% in Group B). In Group A, 50 % had CNS flares at assessment with the remainder having renal flares: 85% & 15% of group A had BILAG scores of A & B respectively. In Group B, 30% & 70% had previous CNS & renal involvement respectively. Of them 2%, 80% and 8% had BILAG scores of C, D, E respectively. The mean NPSLEQ score was 22 in active CNS SLE and 10 in renal flares. Abnormal EEG findings were more common in Group A (70%) compared to Group B (12%) (p =0.002). In group A, those with CNS (90%) and renal flares (50%) had abnormal EEGs (p=0.58). But, temporal lobe changes were more common in active CNS flares (44%) compared to renal flares (0%) (p=0.032). Higher scores on NPSLQ screening were significantly associated with CNS flares (p=0.021) and focal temporal activity (p= 0.038). Temporal changes were also seen in 50% of patients with previous CNS lupus. Lateralisation was not detected in those with focal changes. Conclusions: Abnormal EEGs in SLE were associated with high disease activity and high NPSLQ score. Subjects with active and chronic CNS involvement were more likely to have temporal changes on EEG than those with renal involvement. Temporal EEG changes may be useful in differentiating patients with CNS involvement from those with other system flares. References: Gora MK et al. Wiad Lek. 2003; 56(5-6):220-226. Glanz BI et al. Clin Electroencephalogr. 1998 Jul; 29(3):128-131. Disclosure of Interest: None Declared